Ang "Noli Me Tangere" - Rizal, Jose; Arago, Jorge; Romero, Eddie; Ruiz, Ruby.; Tinio, Rolando; Tiongson, Nicanor; Cultural Center of the Philippines (Manila Cultural Center of the Philippines, 1992)
An adaptation of the novel of Dr. Jose Rizal on Philippine nationalism. This drama series exposes the abusive powers of the Spanish rulers in the Philippines, in particular the Spanish priests.
Episode 1: Crisostomo Ibarra (45 min.) -- Episode 2: Sisa (45 min.) -- Episode 3: Dito po sa amin (45 min.) -- Episode 4: Ang baliw ay pantas (45 min.) -- Episode 5: Nagdidilim ang langit (45 min.) -- Episode 6: Haka-haka at kuro-kuro (45 min.) -- Episode 7: Kaibigang lihim (45 min.) -- Episode 8: Katuwiran at kapangyarihan (45 min.) -- Episode 9: Pagbubunyag (45 min.) -- Episode 10: Bayan o sarili (45 min.) -- Episode 11: Ama ng ikakasal (45 min.) -- Wpisode 12-13: Ang Pasko at ang Bagong Taon (53 min.)
VDR-323 please refer to VDR-1235dgt for digitized version.
Adaptasyon para sa pelikulang pang-telebisyon ni Eddie Romero.
VHS.
Credits: Musical composition and direction Ryan Cayabyab; music, Philippine Philharmonic Orchestra; cinematography, Nap Jamir
Cast: Joel Torre as Crisostomo Ibarra; Maria Jose Arnaldo as Maria Clara
Keywords: Rizal, Jose. Noli Me Tangere -- Film and video adaptations